2017
DOI: 10.1016/j.asjsur.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic surgery under epidural anesthesia for intractable secondary spontaneous pneumothorax

Abstract: In case with patients having intractable SSP with compromised pulmonary function, VATS under EA could be an effective and safe option to approach the appropriate goals of air leak control and less recurrence of pneumothorax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The data of recurrence were reported in four studies [ 8 , 19 , 21 , 22 ]. Because of the homogeneity among these studies ( p = 0.840 and I 2 = 0%), a fixed effect analysis model was used and suggested no difference between the ELA group and GA group (OR = 0.49; 95% CI: 0.15 to 1.55; p = 0.223) ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The data of recurrence were reported in four studies [ 8 , 19 , 21 , 22 ]. Because of the homogeneity among these studies ( p = 0.840 and I 2 = 0%), a fixed effect analysis model was used and suggested no difference between the ELA group and GA group (OR = 0.49; 95% CI: 0.15 to 1.55; p = 0.223) ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the homogeneity among these studies ( p = 0.840 and I 2 = 0%), a fixed effect analysis model was used and suggested no difference between the ELA group and GA group (OR = 0.49; 95% CI: 0.15 to 1.55; p = 0.223) ( Figure 7 ). The four studies [ 19 22 ] reported the related information of perioperative mortality and 6 deaths were recorded in two studies [ 20 , 21 ]. Of them, 2 came from the ELA group [ 21 ] and 4 from the GA group [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations